Accuracy of individualized 3D modeling of ossicles using high-resolution computed tomography imaging data - Zhao, Danheng (Quant Imaging Med Surg, 2021)
BACKGROUND: The present study aimed to investigate the visibility of small ossicle parts/landmarks on high-resolution computed tomography (HRCT)/3D reconstruction (3D) to investigate what improvements in scanning resolution are needed before accurate 3D printing of patient-specific ossicles is possible. METHODS: A total of 24 patients with sudden deafness sought consultation at the Department of Otorhinolaryngology Head and Neck Surgery at the Sixth Medical Center of People’s Liberation Army General Hospital between October 2013 and June 2014 were enrolled in the study. All participants underwent a 256-slice spiral HRCT temporal bone axial scan, yielding a Digital Imaging and Communications in Medicine documents series. These documents were then inputted into Mimics 16.0 interactive medical image processing software for data conversion and the creation of 3D segmentation and visualizations of the ossicles. Finally, the 3D images were compared using multiplanar reformation (MPR) and 3D volume-rendering (VR) reconstructed images of ossicles to verify their consistency. These were then compared with the normal ossicle structure to evaluate the accuracy of the restoration. RESULTS: The findings indicated that the morphology of the ossicles from the converted Mimics 16.0 data achieved a display rate of ≥90% when used to display 7 landmarks (the caput mallei, collum mallei, processus lateralis mallei, manubrium mallei, corpus incudis, crus longum incudis, and crus breve incudis). This demonstrates excellent matching with the images of ossicles obtained from MPR and 3D VR reconstruction. Kappa consistency testing found that the κ-value was higher than 0.75. When displaying the lenticular process, caput stapedis, crus anterius stapedis, and crus posterius stapedis landmarks. The display rate was around 60%, which shows good matching with the ossicles’ images obtained from MPR and 3D VR reconstruction, with a κ-value >0.4. However, the display rate of the stapes footplate was only 25%, showing greater differences with the images obtained from MPR (76.4%) and 3D VR reconstruction (52.8%), with a κ-value <0.4. CONCLUSIONS: The accuracy of the visualization of the malleus and incus after restoration via Mimics 16.0 software, based on temporal bone HRCT data, was high, and the degree of restoration was good. However, the accuracy and degree of restoration of the stapes footplate require further improvement.